A study on water-quenching waste heat recovery from molten slag of slag-tap boilers. (5th September 2016) - Deng, Lei; Tan, Xiaowen; Tang, Chunli; Che, Defu
Highlights: Three water-quenching systems are proposed to recover waste heat from molten slag. The subcooled-water-quenching system can increase the thermal efficiency of unit. The boiling-water-quenching system has the superiority for waste heat recovery. The heating system has a relatively low requirement for the grade of heat source. Abstract: The slag-tap boiler regains great attention due to the utilization of Zhundong coals. To solve high sensible heat loss problem of molten slag, three water-quenching waste heat recovery systems are proposed. For subcooled- and boiling-water-quenching systems, the condensate water can be heated. While for heating system, heating and domestic hot water can be provided. Thermal-economic analyses of these systems are performed based on a typical 220 t h −1 cyclone boiler with nine low-fusion-temperature coals. The results show that the amount of recovered heat is influenced by heating value, ash fusibility and ash content of coal. Ash content is the most important factor. Both of subcooled- and boiling-water-quenching systems can increase the thermal efficiency of unit. The latter system is much simpler and has the superiority for waste heat recovery. Promoting the energy level of waste heat utilization or increasing the temperature of the heated condensate water will certainly increases the thermal efficiency. For the heating system, the heating consumer and bathing pool can be switched according to different regions and seasons. This system has a relatively low requirement for the grade of heat source, although additional pipes with thermal insulation are needed.